Thermal Comfort and Airflow in Air-Conditioned Systems: Insights from Computational Fluid Dynamic Simulations - Jesi Pebralia; Yesi Aryanti; Lucky Zaehir Maulana; Tika Restianingsih; Marita Wulandari (International Journal of Hydrological and Environmental for Sustainability, 2025)
Air conditioning (AC) systems are vital for ensuring thermal comfort in enclosed spaces, particularly in tropical regions like Indonesia, where high temperatures and humidity can challenge human productivity and well-being. This study investigates airflow distribution patterns in air-conditioned rooms using computational fluid dynamics (CFD) simulations, specifically employing the SST k-ω turbulence model. Simulations were conducted in a 3.5 × 3.55 × 3 m closed room with varied inlet temperatures (289.15–297.15 K) and airflow velocities (2–4 m/s). Results indicate that for every 2 K increase in inlet temperature, the average room temperature rises by approximately 1.37 K. Additionally, a 0.5 m/s increment in airflow velocity leads to an average temperature increase of 0.16 K. The airflow was observed to form a dominant jet stream from the AC inlet, flowing diagonally toward the lower part of the room, creating a low-altitude recirculation zone. This phenomenon influences thermal mixing and occupant comfort significantly. Validation of the CFD model revealed its robustness, with an average temperature deviation of 328.15 K and an Nash-Sutcliffe Efficiency (NSE) score of 0.858. Furthermore, the study suggests optimizing AC placement and operation parameters to enhance energy efficiency while maintaining comfort. These findings provide actionable insights into airflow behavior in tropical environments, promoting better design practices for cooling systems, which are crucial for sustainable development and improved living conditions in tropical climates.